International Pediatric Multiple Sclerosis Study Group criteria for pediatric multiple sclerosis and immune-mediated central nervous system demyelinating disorders: revisions to the 2007 definitions - Krupp, Lauren B; Tardieu, Marc; Amato, Maria Pia; Banwell, Brenda; Chitnis, Tanuja; Dale, Russell C; Ghezzi, Angelo; Hintzen, Rogier; Kornberg, Andrew; Pohl, Daniela; Rostasy, Kevin; Tenembaum, Silvia; et al. (Multiple sclerosis, 2013)
Background: There has been tremendous growth in research in pediatric multiple sclerosis (MS) and immune mediated central nervous system demyelinating disorders since operational definitions for these conditions were first proposed in 2007. Further, the International Pediatric Multiple Sclerosis Study Group (IPMSSG), which proposed the criteria, has expanded substantially in membership and in its international scope. Objective: The purpose of this review is to revise the 2007 definitions in order to incorporate advances in delineating the clinical and neuroradiologic features of these disorders. Methods: Through a consensus process, in which input was sought from the 150 members of the Study Group, criteria were drafted, revised and finalized. Final approval was sought through a web survey. Results: Revised criteria are proposed for pediatric acute disseminated encephalomyelitis, pediatric clinically isolated syndrome, pediatric neuromyelitis optica and pediatric MS. These criteria were approved by 93% or more of the 56 Study Group members who responded to the final survey. Conclusions: These definitions are proposed for clinical and research purposes. Their utility will depend on the outcomes of their application in prospective research.